Design, synthesis, and biological evaluation of isatin‐indole‐3‐carboxaldehyde hybrids as a new class of xanthine oxidase inhibitors. Issue 6 (21st March 2022) - Singh, Atamjit; Heer, Shilpa; Kaur, Komalpreet; Gulati, Harmandeep K.; Kumar, Nitish; Sharma, Anchal; Singh, Jatinder V.; Bhagat, Kavita; Kaur, Gurinder; Kaur, Kirandeep; Singh, Harbinder; Chadha, Renu; et al.
Abstract: A novel series of triazole‐linked isatin‐indole‐3‐carboxaldehyde hybrids based on the febuxostat skeleton and its binding site interactions were rationally designed and synthesized as potential xanthine oxidase inhibitors. Among the synthesized hybrids, A19 showed the most potent xanthine oxidase inhibition (IC50  = 0.37 µM) with the mixed‐type inhibitory scenario. Structure–activity relationship studies revealed that methoxy (OCH3 ) substitution on position 5 of the isatin nucleus and a two‐carbon distance between isatin and the triazole moiety is most tolerable for the inhibitory potential. Various binding interactions of A19 with the binding site of xanthine oxidase are also streamlined by molecular docking studies, which showcase the favorable binding pattern for xanthine oxidase inhibition by the hybrid. Furthermore, molecular dynamic studies were performed that suggest the stability of the enzyme–hybrid complex. Overall, the study suggests that hybrid A19 can act as an effective hit lead for further development of potent xanthine oxidase inhibitors. Abstract : Novel triazole‐linked isatin‐indole‐3‐carboxaldehyde hybrids based on the febuxostat skeleton were designed and synthesized as potential xanthine oxidase inhibitors. Among the synthesized hybrids, A19 showed the most potent xanthine oxidase inhibition (IC50  = 0.37 µM) with a mixed‐type inhibitory scenario. Further molecular characterization identifies hybrid A19 as an effective hit lead for the further development of potent xanthine oxidase inhibitors.